Public Social Spending in Korea in the Context of Rapid Population Ageing - Jones, Randall S.. (OECD Economics Department Working Papers, 2008)
Faced with exceptionally rapid population ageing, Korea should address obstacles that lower fertility rates while encouraging higher labour force participation, particularly among women. While public social spending is currently very low, there is pressure for increased outlays on pensions, healthcare, long-term care and social assistance. The government should be cautious in expanding spending, taking into account the impact on economic growth. Outlays should be limited by shifting from direct provision of social services, notably childcare and long-term care, in favour of providing vouchers to consumers. Given the limited coverage of the public pension system, the new means-tested benefit for the elderly will be useful in reducing poverty. It is important to increase transparency about self-employed income to ensure fairness in the financing of social insurance systems, including the new long-term care insurance. The rise in inequality and relative poverty should be reversed by reducing labour market dualism